Analysis of Konya Karatay Madrasah Knotted Kufic Sash Script in terms of Calligraphy and Knot Properties - Berrin Yapar Ünal; Emine Pınar Doğu; Mehmet İşcan (Art-Sanat)
Konya Karatay Madrasah has an important place among the Anatolian Seljuk period buildings in terms of its tiles, geometric decorations and the variety of inscriptions. The knotted kufic sash script made with mosaic tile technique on the dome pulley of the madrasah is a unique example among its counterparts with its rich variety of knots. The characteristic of the knotted kufic calligraphy, which is a type of kufic written subject to geometric principles, is that the vertical extensions of the letters form knots by twisting them with circular or angular lines like a rope. The knot on the script was frequently used as an element of ornamentation in Anatolian Seljuk and Principalities period works. In this study, the photographs of the sash script written in knotted kufic calligraphy on the dome pulley of Konya Karatay Madrasah were digitally sorted side by side and vector drawings were made in digital environment. The inscription’s text readings, typeface, letters, knots and nodes were analyzed, and the letters, knots and nodes used in the writing sash were separated one by one and turned into tables and analyzed. This study aims to document the composition, letters, knots and zulfas of the sash script in Konya Karatay Madrasah. It is hoped to benefit the art of calligraphy by writing new texts with the basic forms of the knotted kufic letters in the sash script.